2019
DOI: 10.1002/jcp.29314
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of dopamine in odontoblasts

Abstract: Dopamine (DA) is produced from tyrosine by tyrosine hydroxylase (TH). A recent study has reported that DA promotes the mineralization of murine preosteoblasts.However, the role of DA in odontoblasts has not been examined. Therefore, in this investigation, we researched the expression of TH and DA in odontoblasts and the effects of DA on the differentiation of preodontoblasts (KN-3 cells). Immunostaining showed that TH and DA were intensely expressed in odontoblasts and preodontoblasts of rat incisors and molar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The released ATP, glutamate, and ADP (which is subsequently hydrolyzed from ATP) establish a paracrine signaling network between odontoblasts through the activation of ionotropic ATP (P2X) receptors, metabotropic glutamate receptors, and metabotropic ADP (P2Y) receptors, respectively; an intercellular odontoblast paracrine/autocrine communication is thereby established. The expression of both DA and TH as well as the DA receptor in odontoblasts [16], taken together with the present results, suggests that DA-induced cAMP signaling following G s protein-coupled DA receptor activation may establish intercellular odontoblast paracrine and/or autocrine communication to promote odontoblastic differentiation and dentinogenesis. However, further studies are required to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The released ATP, glutamate, and ADP (which is subsequently hydrolyzed from ATP) establish a paracrine signaling network between odontoblasts through the activation of ionotropic ATP (P2X) receptors, metabotropic glutamate receptors, and metabotropic ADP (P2Y) receptors, respectively; an intercellular odontoblast paracrine/autocrine communication is thereby established. The expression of both DA and TH as well as the DA receptor in odontoblasts [16], taken together with the present results, suggests that DA-induced cAMP signaling following G s protein-coupled DA receptor activation may establish intercellular odontoblast paracrine and/or autocrine communication to promote odontoblastic differentiation and dentinogenesis. However, further studies are required to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, recent studies have shown that rat odontoblasts are immunoreactive to G s protein-coupled β 2 and calcitonin gene-related peptide (CGRP) receptor antibodies [ 12 , 13 ], and mouse odontoblasts express the parathyroid hormone receptor as observed in in situ hybridization assays [ 14 ]. The immunofluorescent expression of prostaglandin (PG) I 2 (IP) receptors [ 15 ] and the mRNA expression of dopamine (DA) D 1 (D 1 ) receptors in rat odontoblasts have also been reported [ 16 ]. Human dental pulp cells express mRNAs of all four adenosine receptor subtypes (A 1 , A 2A , A 2B , and A 3 receptors) in RT-PCR analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have shown that DA promotes osteoblastic differentiation of bone marrow stem cells and MC3T3-E1 cells 18,19 . Furthermore, in our previous report, we revealed that the involvement of DA in the maturation of odontoblasts at the stage of tooth development 20 . However, there is no report about the effect of DA on odontoblast-like differentiation of DPSCs in the process of reparative dentin formation.…”
mentioning
confidence: 72%
“…Moreover, these factors are expressed in non-neural cells such as those in the heart and pancreas 24,25 . Even in osteoblasts and pre-odontoblasts, these factors are expressed and promote their differentiation 20,26 . Taken together, we demonstrated that TH and DA were involved in odontoblastic differentiation of DPSCs during reparative dentin formation.…”
Section: Discussionmentioning
confidence: 99%
“…A reason for these seemingly conflicting results could be that catecholamine might also be produced by non‐neural cells in the dental pulp. For example, odontoblasts have been verified to express tyrosine hydroxylase, the rate‐limiting enzyme for catecholamine synthesis (Fujino et al., 2020). Importantly, sympathetic nerves tend to mediate the immune response through the release of catecholamine and neuropeptide Y in dental pulp (Haug & Heyeraas, 2005).…”
Section: Discussionmentioning
confidence: 99%